Comparative evaluation of productivity and cost effectiveness of catfish fingerling production in earthen pond and recirculation system in Ibadan, Nigeria (2011)
Despite the popularity of the African catfish and its great market potentials, the production is still basically at subsistence level due majorly to inadequate supply of seed for stocking. This has been linked to the absence of reliable production techniques for the mass production and rearing of the species under practical farming conditions. The purpose of this study therefore, was to find a suitable culture system for the mass production of catfish (Clarias gariepinus) fingerlings. Protected earthen pond and a unit of recirculation system were used. Fertilized eggs from female were divided into two equal halves and incubated under the same conditions. Forty-nine thousand frys each were stocked into the protected earthen pond and a unit recirculation system respectively. The frys in the two systems were raised for twenty one days and fed the same quantity and quality of feed throughout the period. The survival rate of the frys in the recirculation system was 79% as against 17% in the earthen pond. However, bigger sized (2.2 ± 0.23g) fingerlings were obtained from the earthen pond relative to those cultured in the recirculation system (0.9 ± 0.07g). The cost of raising frys in a recirculation system (N34,000) was twice that needed for earthen pond (N17,000), but this was more than made up for in the profit from sales, which was N311,360 and N99,156 respectively. The main reason for fish farming is the expected return to be, therefore, the choice of income-generating activities, amongst several options available, should be made on the grounds of their expected returns.